Interfacial tearing of soft composite gel - Law, Ronald Jin Hua (2019)
Experiment by using Mode 3 fracture along the interface of the soft composite and inhomogeneous has not received an in-depth investigation. In this project, the author will carry out various experiments regarding mode III fracture on soft composite gels, homogeneous and inhomogeneous to see its associated behaviour. Different kinds of concentration to determine the strength and the agar-agar will be used to determine fundamental fracture characteristics such as fracture load, load versus crack propagation and different kind of concentration of the soft gel to obtain experiment results. This will be done by conducting experiments with different level of concentration (20g, 25g, 30g,32g, 35g, 40g, 48g, 56g) to collect data and analyse the fracture properties. Based on the test results, it is concluded that the increase of concentration, increases the critical toughness of the soft composite material to sustain the high load. Larger material concentration improves the fracture properties. In addition, Inhomogeneity ratio able to explore more in-depth of fracture toughness of the soft material and the inhomogeneous agar agar can sustain higher load than homogeneous agar agar. Recommendations for the future development of the experiment are also explored further in the report.